THE EFFECT OF COMPENSATION AND WORKLOAD ON EMPLOYEE PERFORMANCE WITH TURNOVER INTENTION AS A MEDIATION VARIABLE IN SAVE THE CHILDREN INDONESIA - Kurwiany, Kurwiany; Emmanuel Bay Dhirgantara (Dinasti Publisher, 2022)
This study is intended to prove the effect of compensation and workload on turnover intention at Save the Children Indonesia. To find out and analyze the effect of compensation, workload and turnover intention on the performance of Save the Children Indonesia. To prove and analyze the effect of compensation and workload on performance with turnover intention as a mediating variable at Save the Children Indonesia. The population in this study were all 303 employees of Save the Children Indonesia, the probability sampling method was used as a sample and the sampling technique used simple random sampling, the sample amounted to 91 employees at Save the Children. Indonesian children. The analysis data method SEM with the help of the SmartPLS version 3.2.9 program. The results of this study found that compensation has a significant negative effect on turnover intention at Save the Children Indonesia. Workload has a significant negative effect on turnover intention at Save the Children Indonesia. Compensation has a significant positive effect on employee performance at Save the Children Indonesia. Workload has a positive and significant effect on employee performance at Save the Children Indonesia. Turnover intention has a negative and significant effect on the performance of Save the Children Indonesia employees. Compensation provides a positive and significant effect on employee performance mediated by turnover intention at Save the Children Indonesia. Workload has a positive and significant effect on employee performance mediated by turnover intention at Save the Children Indonesia.